(Successful) Democracies Breed Their Own Support - Daron Acemoglu; Nicolas Ajzenman; Cevat Giray Aksoy; Martin Fiszbein; Carlos Molina (Institute of Labor Economics (IZA), 2021)
Using large-scale survey data covering more than 110 countries and exploiting within-country variation across cohorts and surveys, we show that individuals with longer exposure to democracy display stronger support for democratic institutions. We bolster these baseline findings using an instrumental-variables strategy exploiting regional democratization waves and focusing on immigrants' exposure to democracy before migration. In all cases, the timing and nature of the effects are consistent with a causal interpretation. We also establish that democracies breed their own support only when they are successful: all of the effects we estimate work through exposure to democracies that are successful in providing economic growth, peace and political stability, and public goods.
Keywords: P16; 330; democracy; economic growth; institutions; support for democracy; values